Parent Perspectives on Home-Based Intervention for Young Children with Developmental Disabilities: The Parent-Implemented Communication Strategies (PiCS) Project in Illinois, USA - Meadan, Hedda; Stoner, Julia B.; Angell, Maureen E. (Journal of the American Academy of Special Education Professionals, 2015)
Parents’ perspectives on a home-based, parent-implemented social-pragmatic communication intervention for young children aged 37 to 60 months with limited expressive language are presented in this report. The researchers analyzed the perspectives of seven parent participants in the Institute of Education Sciences-funded Parent-Implemented Communication Strategies (PiCS) project and their family members. Data included individual interviews with the parent interventionists, their spouses, and siblings of the target children, external evaluator findings, and survey responses. The research team employed qualitative research methodology to examine family perspectives on the PiCS project. Three major findings emerged concerning the PiCS intervention: (a) the intervention resulted in changes in the interaction between the parent interventionists and the target children, (b) the changed interaction had a positive effect on the children’s social-pragmatic communication skills, and (c) the intervention resulted in positive changes in entire families’ interactions with the target children.